Effects of autochthonous Kluyveromyces lactis and commercial Enterococcus faecium adjunct cultures on the volatile profile and the sensory characteristics of short-ripened acid-curd Cebreiro cheese. (December 2022) - Centeno, Juan A.; Lorenzo, José M.; Carballo, Javier
Abstract: Four batches of Cebreiro-type cheese were made in duplicate from pasteurized milk. A control batch was manufactured with only a commercial O-starter. The other three batches were made with the same starter plus: (i) a commercial culture of Enterococcus faecium ; (ii) a selected Kluyveromyces lactis adjunct culture used in a cheese-milk pre-ripening step; and (iii) the combination of both adjunct cultures. The cheeses made with the yeast adjunct were characterized by higher values of overall proteolysis, pH and aw, and showed total and lactic acid bacteria (LAB) counts at least 2 log units than the batches made with only LAB. The volatile profiles of the cheeses made with added K. lactis were distinguished by high contents of esters, branched-chain alcohols, fatty acids, acetoin and 2-pnenylethanol. These batches had a more friable and sticky texture, and exhibited differential piquant, yeasty, alcoholic, acetic and fruity flavors. Furthermore, the addition of enterococci seemed to help achieve more desirable sensory characteristics. The batches manufactured with both adjunct cultures were awarded the highest scores for texture preference, flavor intensity, flavor preference, and overall sensory preference. The sensory profiles of the cheeses made with added yeast closely resembled those of traditional 'good quality' raw-milk Cebreiro cheese. Highlights: K. lactis and E. faecium adjuncts modify the volatile profile of Cebreiro cheese. K. lactis and E. faecium adjuncts modify the sensory profile of Cebreiro cheese. K. lactis and E. faecium adjuncts add quality and consistency to Cebreiro cheese.